2017
DOI: 10.1142/s2010135x17500011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on structural, dielectric and ferroelectric properties of samarium-substituted BiFeO3–PbTiO3 composites

Abstract: The polycrystalline samples of 0.8BiSm x Fe 1Àx O 3 -0.2PbTiO 3 (x ¼ 0:05; 0:10; 0:15 and 0.20) were prepared by using the conventional solid-state reaction technique and sintered at high temperature (850 C). X-ray diffraction (XRD) confirms the distorted rhombohedral crystal structure for all the composites at room temperature. The surface morphology was checked by field-emission scanning electron microscope (FESEM) technique and homogeneous mixing of the components was confirmed by energydispersive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Recently, Sahu et al have reported enhanced resistivity and relaxor dielectric behavior above room temperature in Gd 3+ modified 0.8BF-0.2PT ceramic samples [31]. The same group also reported the enhancement in dielectric behavior with increase in Sm 3+ doping in 0.8BF-0.2PT solid solutions [32].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Sahu et al have reported enhanced resistivity and relaxor dielectric behavior above room temperature in Gd 3+ modified 0.8BF-0.2PT ceramic samples [31]. The same group also reported the enhancement in dielectric behavior with increase in Sm 3+ doping in 0.8BF-0.2PT solid solutions [32].…”
Section: Introductionmentioning
confidence: 95%
“…A thin film of BiFeO 3 has been demonstrated to show very large polarization [1], but it is deduced that the grain boundaries in a polycrystalline film and defect structures could result in degradation of ferroelectric polarization effects and leakage characteristics. Thus, the need for studies of multiphase or composite oxides based on bismuth iron oxides exhibiting multiferroic properties is very important [4][5][6][7]. To be considered as important, the composite material concerned should exhibit strong coupling effects, for example, between ferroelectric and antiferromagnetic properties [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency semicircle is the grain contribution and the grain boundary contribution comes from the low frequency semicircle. 7,17 The grain conductivity and grain boundary contribution can be calculated 10 with the following equations: where g and gb are conductivity contributed by grain and grain boundary, t is thickness of the samples, A is surface area of the samples, and R g and R gb are resistivity contributed by grain and grain boundary. Table 2 shows the grain and grain boundary conductivity obtained from the equivalent electrical circuit model of the La 1Àx Sr x FeO 3 samples.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the values obtained for dc at all temperatures (T), the conduction activation energy can be calculated using the Arrhenius relation. 8,17 Figure 8 shows the linear relation between 1000/T and ln dc . The conduction activation energy decreased with increasing Sr-substitution.…”
Section: Electrical Propertiesmentioning
confidence: 99%